1997
DOI: 10.1034/j.1600-0501.1997.080506.x
|View full text |Cite
|
Sign up to set email alerts
|

Initial interfacial healing events around calcium phosphate (Ca‐P) coated oral implants

Abstract: The bone response to different calcium phosphate (Ca‐P) coated and non‐coated titanium implants was evaluated in a goat animal model. Two types of Ca‐P coatings have been investigated: an experimental plasma‐spray bi‐layered Ca‐P coating (FA‐HA) and an amorphous RF magnetron sputter coating (Ca‐P‐a). Fifty‐four conical screw shaped implants were inserted in the lateral and medial femoral condyles of 18 Saanen goats. After implantation periods of 3, 12 and 24 days, the bone‐implant interface was evaluated histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 31 publications
1
20
0
Order By: Relevance
“…Many arguments have been made both in opposition to and in favor of the use of HA coatings 34) . This debate has been fueled by the failures of clinical implants, supposedly as a result of poor coating-substrate adherence and problems with the crystallinity of the coating [9][10][11] .…”
Section: Discussionmentioning
confidence: 99%
“…Many arguments have been made both in opposition to and in favor of the use of HA coatings 34) . This debate has been fueled by the failures of clinical implants, supposedly as a result of poor coating-substrate adherence and problems with the crystallinity of the coating [9][10][11] .…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that calcium-phosphate (CaP)-coated endosseous implants exhibit more periimplant bone formation and more bone contact at early healing times than uncoated implants [1][2][3][4][5]. Such bone formation on an implant depends upon the presence of a secretorily active osteoblast population at the implant surface.…”
Section: Introductionmentioning
confidence: 98%
“…Since CaPO 4 do not cause inflammation [307], they could be used as a hard plug deep inside teeth [309]. Finally yet importantly, CaPO 4 crowns were manufactured [518].…”
Section: Biphasic and Multiphasic Capo 4 Formulationsmentioning
confidence: 99%